PENDIDIKAN ANAK USIA DINI DALAM PRESPEKTIF ISLAM - Muhammad Zainuddin Alanshori (JCE (Journal of Childhood Education), 2017)
Early childhood education is a very important element. This paper aims to elaborate the principles of early childhood education based on naqliyah and aqliyah arguments as well as the nature of early childhood education in the Islamic perspectives. In addition, this paper also explains the conceptual theoretical studies of curriculum or content of Islamic education for early childhood, as well as methods that could be applied and developed in the implementation of early childhood education.